BISTUART: BISKUIT RUMINANSIA BERBAHAN DASAR DEDAK DAN BEKATUL DENGAN TAMBAHAN RUMPUT GAJAH DAN TEPUNG TULANG - Muhammad Ilham Bahari; Muhammad Thariq; Farras Abid Abdul Aziz; Tufail Najid; Mahmud Siroth (SMA Trensains Muhammadiyah Sragen, 2023)
Abstract Indonesia is an agrarian country where the livestock sector plays a significant role in its economic growth. The increasing goat population has led to a higher demand for animal feed. One of the byproducts of rice milling is rice bran and rice husk, which amount to 5.4 tons per year. Rice bran and rice husk have good nutritional content for the growth of ruminant animals. In Indonesia, elephant grass thrives and is commonly used as feed for ruminant animals. The aim of this research is to explore the production of BISTUART: ruminant biscuits made from rice bran and rice husk, with the addition of elephant grass and bone meal. This research employs a qualitative descriptive method and literature review, with a focus on the production of BISTUART. Data collection is conducted through observation. Testing includes palatability tests, density tests, moisture content tests, and water absorption tests. The acquired data are analyzed using descriptive methods. Based on the conducted tests, the researchers have successfully identified the effectiveness of BISTUART as an environmentally friendly ruminant feed, as part of the effort to utilize rice milling waste in the form of rice bran and rice husk, enhanced by the fermentation of elephant grass and the addition of bone meal. Keywords: Animal fee, Bone meal, Elephant grass, Rice bran and rice husk Abstrak Indonesia merupakan negara agraris dimana sektor peternakan memiliki peran yang cukup penting dalam pertumbuhan ekonomi Indonesia. meningkatnya populasi kambing membuat pakan yang dibutuhkan juga meningkat. Salah satu limbah penggilingan padi adalah dedak dan bekatul yang mencapai 5,4 ton per tahun, dedak dan bekatul memiliki kandungan yang baik bagi pertumbuhan hewan ruminansia. Di Indonesia rumput gajah dapat tumbuh subur dan sering digunakan sebagai makanan hewan ruminansia. Tujuan penelitian ini adalah untuk mengetahui bagaimana pembuatan BISTUART: biskuit ruminansia berbahan dasar dedak dan bekatul dengan tambahan rumput gajah dan tepung tulang. Jenis metode penelitian yang digunakan menggunakan metode deskriptif kualitatif dan kajian pustaka dengan fokus penelitian pada pembuatan BISTUART. Metode pengumpulan data menggunakan metode observasi. Pengujian yang dilakukan adalah uji palatabilitas, uji kepadatan, uji kadar air, dan uji daya serap air. Data yang telah diperoleh diuraikan menggunakan metode deskriptif. Berdasarkan pengujian yang telah dilakukan, peneliti berhasil mengidentifikasi efektivitas BISTUART sebagai pakan ruminansia yang ramah lingkungan, dalam rangka pemanfaatan limbah penggilingan padi berupa dedak dan bekatul yang ditambah dengan fermentasi rumput gajah dan tepung tulang. Kata Kunci: Dedak dan bekatul, Pakan ternak, Rumput gajah, Tepung tulang